Ion mobility-mass spectrometry reveals conformational flexibility in the deubiquitinating enzyme USP5 - Scott, Daniel; Layfield, Robert; Oldham, Neil J. (Wiley, 2015)
Many proteins exhibit conformation flexibility as part of their biological function, whether through the presence of a series of well-defined states or by the existence of intrinsic disorder. Ion mobility spectrometry, in combination with MS (IM–MS), offers a rapid and sensitive means of probing ensembles of protein structures through measurement of gas-phase collisional cross sections. We have applied IM–MS analysis to the multidomain deubiquitinating enzyme ubiquitin specific protease 5 (USP5), which is believed to exhibit significant conformational flexibility. Native ESI–MS measurement of the 94-kDa USP5 revealed two distinct charge-state distributions: [M + 17H]+ to [M + 21H]+ and [M + 24H]+ to [M + 29H]+. The collisional cross sections of these ions revealed clear groupings of 52 ± 4 nm2 for the lower charges and 66 ± 6 nm2 for the higher charges. Molecular dynamics simulation of a compact form of USP5, based on a crystal structure, produced structures of 53–54 nm2 following 2 ns in the gas phase, while simulation of an extended form (based on small-angle X-ray scattering data) led to structures of 64 nm2. These data demonstrate that IM–MS is a valuable tool in studying proteins with different discrete conformational states.